Study on the Effect of Spur Dike Arrangement in Tidal Estuary on River Bed Scouring - WANG Renchao; ZHANG Gongjin; HU Caixia; LIU Rui; WU Dongdong (Renmin Zhujiang)
There are momentum and mass exchanges between rivers and its adjacent harbors, damfields and river channels. This paper analyzes the influence of different spur dike spacing onriver bed scouring by two-dimensional water-sediment model and theoretical model. The results showthat with the gradual increase of the spur dike spacing, the scouring depth of the dam headincreases slowly, and the scouring distribution in the main channel becomes uneven. Under themaximum flood and ebb velocity, the exchange coefficient of water and sediment between the damfield and the main channel is from 0.01 to 0.04. Under the maximum flood velocity, the exchangecoefficient decreases gradually with the increase of spur dike spacing in linear relationship. Butunder the maximum ebb velocity, the exchange coefficient is the largest when spur dike spacing is4 times longer than dike; and with the increase of spur dike spacing, the average flow velocity inthe main channel decreases gradually. As a whole, the average scouring depth of the main channeldecreases with the increase of spur dike spacing.